Law Enforcement Against Hit-And-Run Cases And The Role Of The Police In Prevention And Prosecution - Rio Saputra; Novritsar Hasitongan Pakpahan; Didit Darmawan; Lutfi Yustyanto Sulaiman; Rio Harton (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Abstract This research aims to analyze law enforcement and moral responsibility in hit-and-run cases as well as the role of the police in preventing traffic accidents. The approach used is descriptive qualitative with the method of document analysis of applicable regulations, literature review, and interpretation of the effectiveness of the policies applied. The results showed that hit-and-run is a criminal offense that has serious legal consequences, as stipulated in Law Number 22 of 2009. The police have a role to take preventive action through socialization and traffic surveillance, as well as repressive action by conducting investigations, arrests, and legal proceedings against the perpetrators. The main factors that encourage hit-and-runs include the perpetrator's fear of legal consequences, panic at the scene, and low public awareness of moral responsibility. The impact is not only in the form of physical and material losses, but also a deep psychosocial impact on victims and their families. Therefore, it is necessary to increase legal awareness in the community and optimize cooperation between the police and related institutions in order to reduce the number of road accidents and violations of the law. Keywords: Accident, Hit-and-run, Law enforcement, Moral responsibility, Police, Prevention Traffic safety,